(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this review paper an overview of the literature is presented from the papers published in last few years. As there is scarcity of petroleum products these days, so the use of vegetable oils in manufacture of polyurethane foam (PU) is increasing day by day. Here, the use of vegetable oils by different researchers in formation of PU foam and characteristics of the foam obtained are highlighted.